Cellular preservation of musculoskeletal specializations in the Cretaceous bird Confuciusornis - Jiang, Baoyu (Nat Commun, 2017)
The hindlimb of theropod dinosaurs changed appreciably in the lineage leading to extant birds, becoming more ‘crouched' in association with changes to body shape and gait dynamics. This postural evolution included anatomical changes of the foot and ankle, altering the moment arms and control of the muscles that manipulated the tarsometatarsus and digits, but the timing of these changes is unknown. Here, we report cellular-level preservation of tendon- and cartilage-like tissues from the lower hindlimb of Early Cretaceous Confuciusornis. The digital flexor tendons passed through cartilages, cartilaginous cristae and ridges on the plantar side of the distal tibiotarsus and proximal tarsometatarsus, as in extant birds. In particular, fibrocartilaginous and cartilaginous structures on the plantar surface of the ankle joint of Confuciusornis may indicate a more crouched hindlimb posture. Recognition of these specialized soft tissues in Confuciusornis is enabled by our combination of imaging and chemical analyses applied to an exceptionally preserved fossil.